2021
DOI: 10.3389/fbioe.2021.696166
|View full text |Cite
|
Sign up to set email alerts
|

Bioaugmentation Technology for Treatment of Toxic and Refractory Organic Waste Water Based on Artificial Intelligence

Abstract: With the development of modern chemical synthesis technology, toxic and harmful compounds increase sharply. In order to improve the removal efficiency of refractory organic matter in waste water, the method of adding powdered activated carbon (PAC) to the system for adsorption was adopted. Through the analysis of organic matter removal rule before and after waste water treatment, it can be found that PAC is easy to adsorb hydrophobic organic matter, while activated sludge is easy to remove hydrophilic and weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Yanbo et al (2021) concluded that adding co-metabolizing substances can improve the COD removal rate of coking wastewater as a result of the promoted growth of bacteria involved in the biodegradation of refractory organic wastewater. They observed that the COD removal rate increased by 1.87% with the addition of glucose as the co-metabolism matrix compared to the control system (Yanbo et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yanbo et al (2021) concluded that adding co-metabolizing substances can improve the COD removal rate of coking wastewater as a result of the promoted growth of bacteria involved in the biodegradation of refractory organic wastewater. They observed that the COD removal rate increased by 1.87% with the addition of glucose as the co-metabolism matrix compared to the control system (Yanbo et al , 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Yanbo et al (2021) concluded that adding co-metabolizing substances can improve the COD removal rate of coking wastewater as a result of the promoted growth of bacteria involved in the biodegradation of refractory organic wastewater. They observed that the COD removal rate increased by 1.87% with the addition of glucose as the co-metabolism matrix compared to the control system (Yanbo et al, 2021). also investigated the biological treatment of coking wastewater with glucose as a carbon source and cometabolic substrate for microbial acclimation.…”
Section: Notes: Genbank Accession Numbers Were Exhibited In Parenthesismentioning
confidence: 99%
“…To reduce the still existing environmental problems concerning phenol pollution worldwide, new and innovative strategies are constantly developed and tested under laboratory conditions before their application in practice on a technical scale. Among these strategies, bioaugmentation using the natural ability of microorganisms (bacteria or fungi) to decompose phenolic compounds is widely and successfully applied in the recultivation of phenol-contaminated soil and wastewater [10,47,48]. However, not all microorganisms that can degrade phenol and its derivatives in the established optimal laboratory conditions can be introduced into contaminated sites to enhance the degradation potential of the indigenous microbiome.…”
Section: Statistical Data Explorationmentioning
confidence: 99%